EFEKTIVITAS WAKTU TERAPI MUSIK LANGGAM JAWA TERHADAP TEKANAN DARAH PADA LANSIA HIPERTENSI DI DESA MUARA RENGAS - Putri, Aridayanti Fajar; Muflih, Muflih; Damayanti, Santi (Coping: Community of Publishing in Nursing; Vol 8 No 2 (2020): Agustus 2020, 2020)
When listening to music, the body responds releasing dopamine from the body. The release of dopamine causes vasodilation of blood vessels so that it will affect a person's blood pressure. The standard length of time for Javanese  langgam  music therapy in previous studies was found to be different. Therefore, it is necessary to do research to compare its effectiveness.The purpose of this research to determine the effectiveness of Javanese  langgam  music therapy time on blood pressure in elderly persons with hypertension in Muara Rengas village. This research uses a quasi-experimental method with pre and post control design, the selection of respondents uses a non-probability sampling with a consecutive sampling method. The Wilcoxon test, Paired T-Test, Mann Whitney and Independent T-Test show there is an effect of Javanese  langgam  music therapy on blood pressure in elderly persons with hypertension in the 15-minute group with a systolic p value of 0.000 (<0.05) and a diastolic p value of 0.013; and in the 30-minute group with a p value of 0.008 (<0.05) and a diastolic p value of 0.029 (<0.05). There is no effectiveness difference on blood pressure after being given Javanese music intervention for 15 minutes and 30 minutes with a systolic p value of 0.320 (>0.05) and a diastolic p value of 0.576 (> 0.05). Based on research results there is no effectiveness difference between 15-minute and 30-minute Javanese  langgam  music intervention in elderly persons with hypertension.